WHEY PROTEIN SUPPLEMENTATION IMPROVES LUNG FUNCTION, FUNCTIONAL CAPACITY, AND RESPIRATORY AND PERIPHERAL MUSCLE STRENGTH IN HEALTHY OLDER ADULTS (CIPEEX, 2025)
The elderly population often faces a decrease in calorie and protein intake, a phenomenon that plays a key role in the marked loss of muscle mass and strength. This nutritional decline is directly associated with the weakening of muscle reserves, which can manifest itself in several adverse health consequences. The reduction in the intake of essential nutrients compromises not only the structural integrity of muscles, but also their functional capacity (CHEN et al, 2022).The effects of this muscle loss are far-reaching and affect various aspects of physical and respiratory function. The decrease in muscle mass has direct implications for respiratory and peripheral strength, significantly affecting the efficiency with which the body performs vital functions. This deterioration in strength and functional capacity can lead to widespread impairment of lung function, highlighting the importance of maintaining adequate nutrition to preserve the health and well-being of older adults (CHEN et al, 2022).